PENGARUH PEMBERIAN EKSTRAK DAUN BIDARA (Zizipus mauritiana Lam.) TERHADAP FUNGSI HATI TIKUS DENGAN PARAMETER SGPT - Amirah, Sitti; Rahman, Safriani; Fitriana, Fitriana; Wati, Aulia; Putra, Bayu; Rakhmat, Syahgita; Mustakim, Putri Dwiyanti Adha; Resvani, Syahyu; Hasbullah, Nurhijjah; Arini, Arini (Fakultas Farmasi UMI, 2024)
Repeated administration of traditional medicines can be potentially poisonous and damage vital organs such as the heart, lungs, liver and kidneys. Tests of safety need to be carried out. Bidara leaves are used traditionally used as antimicrobial, analgesic, antipyretic, anti-inflammatory, anti-diabetic. This study aims to determine safety of ethanol extract of bidara leaves on liver function. This research used wistar rats as test animals which were divided into 4 groups. Test animals were given ethanol extract of bidara leaves at a dose of 50 mg/kgBW, 500 mg/kgBW and 2000 mg/kgBW given orally for 14 days. SGPT rate checks are carried out before and after administering the extract. The results showed that giving ethanol extract of bidara leaves for 14 days did not have a significant effect on rat SGPT levels (p<0.05).